A one‐to‐one programme for at‐risk readers delivered by older adult volunteers. Issue 3 (19th December 2013) - Fives, Allyn; Kearns, Noreen; Devaney, Carmel; Canavan, John; Russell, Dan; Lyons, Rena; Eaton, Patricia; O'Brien, Aoife
<x xml:space="preserve">Abstract</x> This paper is based on a randomized controlled trial (RCT) evaluation of a reading programme delivered by older adult volunteers for at‐risk early readers. Wizards of Words (WoW) was targeted at socially disadvantaged children in first and second grade experiencing delays in reading but who were not eligible for formal literacy supports. The programme was effective for phonemic awareness, word recognition, phonic knowledge and children's self‐beliefs, but was not effective for reading comprehension, vocabulary, spelling or reading accuracy. The programme was most effective for those children starting with 'below average' reading levels and for boys. Programme intensity, school attendance and the child's experience of the programme all predicted response to intervention. Gains in phonemic awareness and phonic knowledge may be explained by the priority given in volunteer training and in programme delivery to the phonics component, and gains in word recognition may be explained by its close association with phonemic awareness and phonic knowledge, as hypothesized by the Simple View of Reading. The findings show that a reading programme delivered by older adult volunteers can have a significant impact on reading skills and self‐beliefs of at‐risk readers who are not eligible for other formal literacy supports.